1992
DOI: 10.1063/1.108300
|View full text |Cite
|
Sign up to set email alerts
|

Laser performance of Cr4+:Y2SiO5

Abstract: Laser action in chromium-activated forsterite for near-infrared excitation: Is Cr 4+ the lasing ion?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
3

Year Published

1995
1995
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(27 citation statements)
references
References 2 publications
0
24
0
3
Order By: Relevance
“…doped Y 2 SiO 5 crystals to be used as blue phosphor or Cr 4+ -doped Y 2 SiO 5 as a saturable-absorber Q-switch laser. [8][9][10] As an important phase in the SiO 2 -Y 2 O 3 -Si 3 N 4 phase diagram, 11,12 Y 2 SiO 5 is frequently identified as a precipitated phase at the grain boundaries of sintered Si 3 N 4 with Y 2 O 3 or Y 2 O 3 + SiO 2 as sintering aids. And it is confirmed that Y 2 SiO 5 can improve the high-temperature performance of silicon nitride.…”
Section: Introductionmentioning
confidence: 99%
“…doped Y 2 SiO 5 crystals to be used as blue phosphor or Cr 4+ -doped Y 2 SiO 5 as a saturable-absorber Q-switch laser. [8][9][10] As an important phase in the SiO 2 -Y 2 O 3 -Si 3 N 4 phase diagram, 11,12 Y 2 SiO 5 is frequently identified as a precipitated phase at the grain boundaries of sintered Si 3 N 4 with Y 2 O 3 or Y 2 O 3 + SiO 2 as sintering aids. And it is confirmed that Y 2 SiO 5 can improve the high-temperature performance of silicon nitride.…”
Section: Introductionmentioning
confidence: 99%
“…)-doped Y 2 SiO 5 crystals used as blue phosphor or Cr 4+ -doped Y 2 SiO 5 as saturable-absorber Q-switch laser. [2][3][4] As an important phase in the SiO 2 -Y 2 O 3 -Si 3 N 4 phase diagram, Y 2 SiO 5 is frequently identified as a precipitated phase at the grainboundaries of sintered Si 3 N 4 with Y 2 O 3 or Y 2 O 3 + SiO 2 as sintering aid. [5][6][7] And it has been proven that Y 2 SiO 5 has the capability of improving the high-temperature performance of silicon nitride.…”
Section: Introductionmentioning
confidence: 99%
“…The CW laser output power is given in mW, W, kW. In understanding some date see also GeO 4 , and LiScGeO 4 crystals doped with chromium ions has also been the subject of detailed studies [268][269][270][271]. It is possible that lasing chromium has only a four-valence state in these compounds [270][271][272][273][274][275].…”
Section: Laser Spectroscopic Potential Of Transition Metal Ionsmentioning
confidence: 99%